An Analysis of Translation Techniques Used in Translating a Religious Story from Arabic into English: A Case Study - khairy Mahammad Abubaker Khaleeda Rashed (Journal of Scientific and Human Dimensions, 2026)
This study investigates the techniques used in translating an Arabic religious story into English, focusing on the translator's ability to maintain fluency and preserve cultural nuances. Using Vinay and Darbelnet’s (1995) model, the research employs a qualitative case study design with a purposive sample of six critical textual segments. The analysis reveals that literal translation (33%) and borrowing (28%) were the most frequent methods. While effective for factual accuracy, the overuse of literalism occasionally hindered idiomatic fluency (e.g., "secretary of revelation"). The study concludes that a strategic balance between modulation and literal translation is essential for translating religiously sensitive texts and provides pedagogical recommendations for translation training.
Keywords: Translation Techniques; Arabic-English Translation; Vinay and Darbelnet; Literal Translation; Borrowing; Modulation; Adaptation; Religious Texts